Perception of the socialisation influence of the Osun radio’s programme ‘OMOLUABI’ (2016)
"Omoluabi", a programme on Osun State radio, is a motivational radio programme which addresses various issues that affect human life. Hence, the study was design to investigate the influence of the radio programme on the behaviour and attitudes of the people within Osun State. The study is framed by the Agenda Setting theory. It adopts qualitative and quantitative research methods with questionnaire and interview guide as tools for data gathering. The purposive sampling technique was employed to select for the survey aspect of the study respondents who were 18 years and above. Interviews were conducted with key producers of the radio programmes. Data gathered were analysed using the simple percentage counts and issues of interest in the interviews were also coded to support the findings of the study. Findings revealed that 'Omoluabi' programme has been educative, informative, didactic, thereby inculcating positive social attitude in the people of Osun State. Also, the study revealed that 'Omoluabi' programme contributed an appreciable percentage to positive influence in the promotion of the usage of the mother tongue (language), and this influences the majority of listeners to avoid anti-social behaviours and become socially responsible to the government and the people in their environment. However, funding constitutes a major challenge to the continuity of the programme. The study confirms the social influence of radio and recommends that more radio programmes should be designed to promote development that would drive socialization among the populace.